Anterior segment optical coherence tomography measurement after neodymium-yttrium-aluminum-garnet laser capsulotomy - Eliaçık, Mustafa; Bayramlar, Hüseyin; Karaman Erdur, Sevil; Demirci, Göktu?; Gülkılık, Gökhan (Elsevier, 2014)
Purpose: To evaluate changes in anterior chamber depth (ACD) and angle width after neodymium- yttrium-aluminum-garnet (Nd:YAG) laser capsulotomy.Design: Prospective interventional case series.Methods: In a single institution, 43 eyes of 43 consecutive pseudophakic patients with symptomatic posterior capsule opacification (PCO) underwent Nd:YAG laser capsulotomy. Anterior chamber depth and angle width in pseudophakic eyes with posterior capsule opacification were measured with anterior segment optical coherence tomography (AS-OCT) before and 3 days after Nd:YAG laser capsulotomy. Preoperative and postoperative measurements of anterior chamber depth and angle width included the angle opening distance, measured as the perpendicular distance from the trabecular meshwork at 500 mm and 750 mm anterior to the scleral spur to the anterior iris surface (AOD500 and AOD750, respectively), and anterior chamber angle (ACA) in the nasal and temporal quadrants. Main outcome measures were the changes in ACD and angle width parameters.Results: The mean patient age was 63.4 ± 3.6 years. Before Nd:YAG laser capsulotomy, mean ACD, AOD500, AOD750, and ACA (nasal and temporal) measurementswere 3.71 ± 0.11mm, 0.61 ± 0.054mm, 0.67 ± 0.063 mm, and 34.5 ± 1.67 degrees and 34.8 ± 1.55 degrees, respectively. Three days after Nd:YAG laser capsulotomy, mean ACD, AOD500, AOD750, and ACA (nasal and temporal) measurements were 3.77 ± 0.1 mm, 0.69 ± 0.06 mm, 0.73 ± 0.06 mm, and 35.51 ± 1.64 degrees and 36.17 ± 1.51 degrees, respectively (P <.01 for all).Conclusion: The depth and width of the ACA in pseudophakic eyes with PCO increased significantly after Nd:YAG laser capsulotomy, as shown by AS-OCT, a reliable and noncontact method for measuring anterior ocular structures. Our study shows that the different angle parameters such as ACD, AOD500, AOD750, and ACA measurements seem highly correlated.
Keywords: Posterior Capsular Opacification; Reproducibility; Yag Laser; Ultrasound Biomicroscopy